Gender Differences in Selection of Investment Avenues in Solan Town of Himachal Pradesh - Kashyap, Neha; Bansal, Arshia; Mehta, Piyush; Kumar, Raina Krishan (International Journal of Bio-resource and Stress Management, 2019)
The study was conducted at Solan town of Himachal Pradesh. It has highlighted the key areas of gender differences in the selection of investment avenues in a very substantive manner.The study was undertaken with the objective of knowing the various investment avenues available to household investors and the factors influencing investment decision making and also the significant differences in factor influencing decision making with respect to gender. While studying the awareness level of the investors about the various investment avenues available, it was observed that males were largely inclined for investment options involving high risk, whereas females were more attracted towards the traditional investment avenues like gold and silver. Study revealed that the female gender are risk averse and invest small amount of their income in low risk investment avenues whereas male gender are risk seekers and invest larger part of their income in diversified investment avenues involving high risk. The comparative analysis found that the male respondents were more interested towards real-estate and the female respondents were active towards bank fixed deposits. Male investors prefer growth and income component whereas female investors were inclined for long-term growth component and safety aspect of investment. Most of the males and females respondents who have invested are from the mid age the investment companies should invent new investment schemes for targeting the other age group people. The investment companies should make new schemes which are less risky so that the mid income group people could also invest.